STUDY ON SPATIAL CHARACTERISTICS ON RUMAH PANGGONG IN SIJUK DISTRICT, BANGKA BELITUNG - Dimas Wihardyanto; Sherlia . (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
Rumah Panggong is a form of local architecture in Belitung Island, where there are not many architectural studies focusing on it. This study focused on the spatial aspect, because space is the firstly generated architectural design idea to facilitate activities or society culture before later developed into the form, structure, materials, and so forth. The approach used was qualitative descriptive with emphasis on data collection method using field observations, as well as data analysis method using a coding system, which included open coding, axial coding phase and selective coding phase. Through this research, it was found that Rumah Panggong is formed into 3 parts, namely mother room, suyok or porch, and cesspit. These 3 parts form the typo-morphology of the building. The basic spatial ideas of Rumah Panggong can be identified by its functionality, effectiveness, flexibility and most essentially its mother room existence.